Pengaruh Cyber Bullying di Era Digital Pada Remaja - Silviana Aulia Putri; Putri Fauziah; Ilham Hudi; Ine Hanisa Pratama; Mega Sari Indah Yani; Rika Novriyanti; Devi Nila Anjani; Aisyah Rahmatul Fitri (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
The aim of this research is to determine the impact of Cyber Bullying in the digital era during adolescence. This research uses a literature review study method. This research found results in the form of the influence of Cyber Bullying in the digital era during adolescence. Based on a literature review study, it was found that the current generation of teenagers will have a good education in both the real and virtual worlds. Indicators of the causes of Cyber ​​Bullying are 1) Anonymity: The freedom to remain anonymous while using the internet can encourage people to act violently without worrying about facing immediate repercussions. 2) Lack of Empathy: When a perpetrator is physical. The aim of the research is to determine the impact of Cyber Bullying in the digital era on teenagers.